Sosialisasi Lima Perilaku Berisiko Dalam Berkendara di SMA/SMK Jakarta dan Bekasi - Fitrina, Rehani; Ruminda, Marthaleina; Firdaus, Muhamad Iqbal; Widiyantoe, Prima (Jurnal Abdimas Transportasi & Logistik, 2025)
Awareness of motorcycle driving safety entails monitoring your own and other drivers' conditions in traffic. Counseling and socialization of five motorcycle riding behaviors is needed to promote safety. The implementation of this socialization was in 3 (three) schools with different locations. The socialization method uses soft skills and hard skills methods, namely providing theory and tutorials, independent practice, discussion and question-and-answer. The activity was carried out for 3 (three) days, so that the total was 24 hours. The findings of this service activity show an increase in understanding and awareness of the importance of applying theory and tutorials in driving. The increase is known based on the results of the pre-test and post-test of participants. The implementation of this community service program is expected to reduce the rate of accidents in driving. In addition, students can volunteer and conduct education regularly and continuously in each generation.